Digital Agriculture, Agricultural Mechanization and Food Security in Nigeria - M.O., Ale; A.S., Oluwalami (International Journal of Scientific Research in Computer Science and Engineering, 2024)
This paper highlights the crucial role of digital agriculture in agricultural mechanization for achieving food security in Nigeria amidst the challenges posed by a growing population, climate change, and declining agricultural productivity. The study explores the transformative potential of digitalization like precision agriculture, remote sensing, and data analytics in complimenting traditional agricultural practices. It also provides an overview of digital agriculture and agricultural mechanization as essential factors required for optimum food production to fight hunger and poverty in Nigeria. It explores the potential benefits and limitations of the use of digital technologies in precision farming. It also discusses the challenges facing the adoption of digital agriculture for the mechanization of agriculture in Nigeria. Among them are inadequate digital infrastructures, limited technical capacity and insufficient investment. Fostering a supportive policy environment and public private partnerships are recommended to promote the adoption of digital agriculture for sustainable agricultural mechanization to achieve food security and poverty alleviation in Nigeria.